Characterization of a multilayer ionization chamber prototype for fast verification of relative depth ionization curves and spread-out-Bragg-peaks in light ion beam therapy - Mirandola, Alfredo; Magro, Giuseppe; Lavagno, Marco; Mairani, Andrea; Molinelli, Silvia; Russo, Stefania; Mastella, Edoardo; Vai, Alessandro; Maestri, Davide; La Rosa, Vanessa; Ciocca, Mario (Medical physics, 2018)
PURPOSE: To dosimetrically characterize a multilayer ionization chamber (MLIC) prototype for quality assurance (QA) of pristine integral ionization curves (ICs) and spread-out-Bragg-peaks (SOBPs) for scanning light ion beams. - METHODS: QUBE (De.Tec.Tor., Torino, Italy) is a modular detector designed for QA in particle therapy (PT). Its main module is a MLIC detector, able to evaluate particle beam relative depth ionization distributions at different beam energies and modulations. The charge collecting electrodes are made of aluminum, for a nominal water equivalent thickness (WET) of ~75 mm. The detector prototype was calibrated by acquiring the signals in the initial plateau region of a pristine BP and in terms of WET. Successively, it was characterized in terms of repeatability response, linearity, short-term stability and dose rate dependence. Beam-induced measurements of activation in terms of ambient dose equivalent rate were also performed. To increase the detector coarse native spatial resolution (~2.3 mm), several consecutive acquisitions with a set of certified 0.175-mm-thick PMMA sheets (Goodfellow, Cambridge Limited, UK), placed in front of the QUBE mylar entrance window, were performed. The ICs/SOBPs were achieved as the result of the sum of the set of measurements, made up of a one-by-one PMMA layer acquisition. The newly obtained detector spatial resolution allowed the experimental measurements to be properly comparable against the reference curves acquired in water with the PTW Peakfinder. Furthermore, QUBE detector was modeled in the FLUKA Monte Carlo (MC) code following the technical design details and ICs/SOBPs were calculated. - RESULTS: Measurements showed a high repeatability: mean relative standard deviation within ±0.5% for all channels and both particle types. Moreover, the detector response was linear with dose (R2 > 0.998) and independent on the dose rate. The mean deviation over the channel-by-channel readout respect to the reference beam flux (100%) was equal to 0.7% (1.9%) for the 50% (20%) beam flux level. The short-term stability of the gain calibration was very satisfying for both particle types: the channel mean relative standard deviation was within ±1% for all the acquisitions performed at different times. The ICs obtained with the MLIC QUBE at improved resolution satisfactorily matched both the MC simulations and the reference curves acquired with Peakfinder. Deviations from the reference values in terms of BP position, peak width and distal fall-off were submillimetric for both particle types in the whole investigated energy range. For modulated SOBPs, a submillimetric deviation was found when comparing both experimental MLIC QUBE data against the reference values and MC calculations. The relative dose deviations for the experimental MLIC QUBE acquisitions, with respect to Peakfinder data, ranged from ~1% to ~3.5%. Maximum value of 14.1 μSv/h was measured in contact with QUBE entrance window soon after a long irradiation with carbon ions. - CONCLUSION: MLIC QUBE appears to be a promising detector for accurately measuring pristine ICs and SOBPs. A simple procedure to improve the intrinsic spatial resolution of the detector is proposed. Being the detector very accurate, precise, fast responding, and easy to handle, it is therefore well suited for daily checks in PT.
Gesehen am 23.04.2020